Erythropoietin for the treatment of anemia in patients with hematologic disorders - R. A. Podgurskaya; V. V. Pshibieva (Онкогематология)
This article introduces common data and our experience concerning the treatment with recombinant human erythropoietin anemia (r-HuEPO) in anemic patients with different disorders. We cited as an example some results of Eprex (Janssen-Cilag) therapy for patients with hematologic disorders in Russia. 28 anemic patients treated with Eprex were included in a single center study (CLL 8, lymphomas 2, CIMF 11, MDS 5, AA 2). The majority of patient demonstrated stable increase in hemoglobin levels and erythrocyte counts, improvement of performance status and decrease in transfusion requirements. Erythropoietin was well tolerated. Further studies in order to value long-term effect of Eprex are in progress.